TRADE INDUCED MORTALITY - Adda, Jérome; Fawaz, Yarine (L'Actualité économique, 2019)
This paper evaluates the effect of increased trade on the mortality of workers in the manufacturing sector. We exploit the large increase of Chinese exports in the last two decades to assess its effect in two different countries, Italy and the US. Exploiting individual longitudinal data, we find that trade leads to an increased mortality rate among these populations, the effect being higher in Italy than in the US. A one billion dollar increase in imports leads to a 4 percent mortality increase in the US and up to 7 percent in Italy. We show that mortality patterns are different across occupational groups, with a more pronounced effect on blue-collar workers in the US and in Italy, a marked effect on managers of small firms. We show that there are important spatial inequalities in the mortality burden of trade.